Wybrane aspekty wykorzystania biomasy drzewnej do celów energetycznych - Gołos, Piotr; Kaliszewski, Adam (Leśne Prace Badawcze, 2016)
This article presents the most important aspects relevant to forest-derived biomass utilization for the purposes of energy production by professional energy providers. The issues discussed here are divided into four groups: environmental, social, economic and technological aspects of biomass utilization in energy production. The environmental part focuses on the effects of intensive use of leftovers from timber harvest on forest ecosystems as well as the problem of ash utilization. Economic and social problems include the costs of energy production from timber, consequences of intensified fuel wood demand for the state of the timber and paper industry as well as the impact on the labor market. The technology section of the article covers questions related to the harvest and transport of forest-derived biomass. We conclude that, before regarding it as an energy source, wood should be mainly used for the production of timber due to the necessity and difficulty of considering all of the above-mentioned diverse aspects of energy production. Wood should be used for the production of energy only after its usage as timber products and their recycling.